Can we use postal surveys with anonymous testing to monitor chlamydia prevalence in young women in England? Pilot study incorporating randomised controlled trial of recruitment methods. (20th August 2015) - Woodhall, Sarah C; Nichols, Tom; Alexander, Sarah; da Silva, Filomeno Coelho; Mercer, Catherine H; Ison, Catherine; Gill, O Noel; Soldan, Kate
Abstract : Objectives: Chlamydia prevalence in the general population is a potential outcome measure for the evaluation of chlamydia control programmes. We carried out a pilot study to determine the feasibility of using a postal survey for population-based chlamydia prevalence monitoring. Methods: Postal invitations were sent to a random sample of 2000 17-year-old to 18-year-old women registered with a general practitioner in two pilot areas in England. Recipients were randomised to receive either a self-sampling kit (n=1000), a self-sampling kit and offer of £5 voucher on return of sample (n=500) or a self-sampling kit on request (n=500). Participants returned a questionnaire and self-taken vulvovaginal swab sample for unlinked anonymous Chlamydia trachomatis testing. Non-responders were sent a reminder letter 3 weeks after initial invitation. We calculated the participation rate (number of samples returned/number of invitations sent) and cost per sample returned (including cost of consumables and postage) in each group. Results: A total of 155/2000 (7.8%) samples were returned with consent for testing. Participation rates varied by invitation group: 7.8% in the group who were provided with a self-sampling kit, 14% in the group who were also offered a voucher and 1.0% in the group who were not sent a kit. The cost per sample received was lowest (£36) in the group who were offered both a kit and a voucher. Conclusions: The piloted survey methodology achieved low participation rates. This approach is not suitable for population-based monitoring of chlamydia prevalence among young women in England. Study registration number: (UKCRN ID 10913).